Data and Democracy: Social Media Analytics in Political Campaign Strategies - Sheikh, Suhail Ahmad (International Journal of English Literature and Social Sciences (IJELS), 2024)
This research explores the intricate relationship between social media and politics, focusing on the impact of digital media on political communication and engagement. The examined literature encompasses diverse dimensions, including the logic of connective action in contentious politics, the role of social media during uprisings, and the evolving landscape of election campaigns with platforms like Twitter. Case studies scrutinize the use of social media analytics in campaigns, shedding light on predictive modelling, personalized messaging, and ethical challenges. The study delves into the intersection of technology and democracy, emphasizing the power dynamics in play. The analysis extends to the global context, exploring online practices and the influence of social media on various movements. As a comprehensive review, this research contributes to understanding the multifaceted dynamics of social media’s influence on political processes.